Therapeutic drug monitoring of vancomycin by AUCτ-MIC ratio in patients with chronic kidney disease - Ahmad Khoei; Rasool Soltani; Jaber Emami; Shirinsadat Badri; Shahram Taheri (Wolters Kluwer Medknow Publications, 2019)
In this study which was conducted in Alzahra University Hospital (Isfahan, I.R. Iran), the therapeutic drug monitoring of vancomycin focused on determining area under the concentration-time curve at dosing interval (τ) at steady state/minimum inhibitory concentration (AUCτ/MIC) was carried out in chronic kidney disease (CKD) patients. The study population was selected from patients with the history of CKD (stages 3 or 4) treated by intravenous vancomycin. To determine vancomycin AUCτ, blood samples were taken at four different occasions (trough-1, peak, random, trough-2) between the fourth and fifth doses of vancomycin. Drug concentration was determined by fluorescence polarization technique, and the E-TEST technique was used to determine the MIC. Nineteen patients were included. For 8 (42%), 7 (37%), and 4 (21%) patients, trough concentration levels were found to be less than 10 mg/L, 10-20 mg/L, and more than 20 mg/L, respectively. The mean value of AUCτ for studied patients was 470.7 ± 228.3 mg.h/L and the mean MIC values was 1.04 ± 0.43 mg/L. Ten patients (53%) and 9 patients (47%) had the AUCτ/MIC ratios above 400 and below 400, respectively, with the average of 519.4 ± 391.3 h. Vancomycin dosing based on patient glomerular filtration rate (GFR), as a traditional method, is not accurate enough to gain the most desired vancomycin concentration in patients with decreased or changing kidney function. Measuring drug concentration and observing its therapeutic effects accordingly is inevitable in susceptible populations receiving vital drugs such as vancomycin.